1986
DOI: 10.1007/bf00218080
|View full text |Cite
|
Sign up to set email alerts
|

Association between microtubules and mitochondria in myelinated axons of Lacerta muralis

Abstract: The spatial relationship between microtubules and mitochondria was studied in myelinated axons of the ventral and dorsal spinal roots of the lizard Lacerta muralis by use of quantitative methods in single and serial sections. Microtubules mainly occurred in groups of 3 to 10. The mean density of microtubules was found to be significantly higher close to mitochondria than in the rest of the axoplasm. In single sections, 59-62% (according to the root region examined) of the microtubule groups were found to be 'a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…SNPH likely acts as a docking receptor specific for axonal mitochondria through a unique interaction with the microtubule-based cytoskeleton. These findings provide a molecular explanation for the previously identified biochemical interactions between neuronal mitochondria and microtubules (Linden et al, 1989; Jung et al, 1993; Leterrier et al, 1994), and morphological observations of axonal ultrastructures, which revealed cross-bridges between mitochondria and microtubules in vivo (Smith et al, 1977; Hirokawa, 1982; Benshalom and Reese, 1985; Pannese et al, 1986; Price et al, 1991). These cross-bridges may represent both dynamic (motor proteins) and static links (docking or anchoring proteins) between axonal mitochondria and the microtubule-based cytoskeleton.…”
Section: Syntaphilin Acting As a “Static Anchor” For Docking Axonal Msupporting
confidence: 60%
“…SNPH likely acts as a docking receptor specific for axonal mitochondria through a unique interaction with the microtubule-based cytoskeleton. These findings provide a molecular explanation for the previously identified biochemical interactions between neuronal mitochondria and microtubules (Linden et al, 1989; Jung et al, 1993; Leterrier et al, 1994), and morphological observations of axonal ultrastructures, which revealed cross-bridges between mitochondria and microtubules in vivo (Smith et al, 1977; Hirokawa, 1982; Benshalom and Reese, 1985; Pannese et al, 1986; Price et al, 1991). These cross-bridges may represent both dynamic (motor proteins) and static links (docking or anchoring proteins) between axonal mitochondria and the microtubule-based cytoskeleton.…”
Section: Syntaphilin Acting As a “Static Anchor” For Docking Axonal Msupporting
confidence: 60%
“…Given that the sequence of SNPH is not homologous to any known microtubule-binding protein in the database, SNPH likely acts as a docking receptor specific for axonal mitochondria through a unique interaction with the microtubule-based cytoskeleton. These findings provide a molecular explanation for the biochemical interactions between neuronal mitochondria and microtubules (Linden et al, 1989;Jung et al, 1993;Leterrier et al, 1994), and morphological observations of axonal ultra-structures, which revealed cross-bridges between mitochondria and microtubule in vivo (Smith et al, 1977;Hirokawa, 1982;Benshalom and Reese, 1985;Pannese et al, 1986;Price et al, 1991). These cross-bridges may represent both dynamic (motor proteins) and static (docking or adaptor proteins) links between axonal mitochondria and the microtubule-based cytoskeleton.…”
Section: Snph Docks Axonal Mitochondria Through An Interaction With Mmentioning
confidence: 73%
“…This indicates that there might be an apparatus for specific mitochondrial docking. Although most of the cross-bridges observed between mitochondria and the axonal cytoskeleton in vivo (Smith et al, 1977;Hirokawa, 1982;Benshalom and Reese, 1985;Pannese et al, 1986;Hirokawa and Yorifuji, 1986;Price et al, 1991) now seem to be dynamic (perhaps motor proteins themselves), others are likely to represent more static links. Indeed, the specialized presynaptic region of the calyx of Held contains a mitochondrion-associated adherens complex, a clearly observable physical substrate for holding and organizing the mitochondria (Rowland et al, 2000).…”
Section: Motor Receptorsmentioning
confidence: 99%